2006
DOI: 10.1590/s0004-27492006000300006
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre a espessura corneana e a gravidade de defeito de campo visual no glaucoma primário de ângulo aberto

Abstract: The central corneal thickness measurement is desirable when establishing target intraocular pressure of patients with open-angle glaucoma. Central corneal thickness is a clinical factor in determining glaucoma severity. Patients with severe field loss showed lower corneal thickness compared with patients with mild and moderate visual field loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…We found an association between CCT and glaucoma, driven by CST rather than CET. Furthermore, similar to previous reports, 29, 30 we found a correlation between decreased CCT and increased glaucoma severity. However, when controlling for race, we found that black race was more significantly associated with CST than the presence or absence of glaucoma.…”
Section: Discussionsupporting
confidence: 92%
“…We found an association between CCT and glaucoma, driven by CST rather than CET. Furthermore, similar to previous reports, 29, 30 we found a correlation between decreased CCT and increased glaucoma severity. However, when controlling for race, we found that black race was more significantly associated with CST than the presence or absence of glaucoma.…”
Section: Discussionsupporting
confidence: 92%
“…This finding has been recorded in other studies. 8,912,16,17 The inverse correlation between CCT and VF stage underlines the importance of taking into consideration the corneal thickness in the long-term strategy of treatment of POAG. Underestimation of the IOP during long-term therapy is one of the possible explanations for this correlation.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,10,11,12 The purpose of this study is to determine the relationship between central corneal thickness (CCT) and the severity of POAG in Hispanics as determined by the severity of the visual field loss.…”
Section: Introductionmentioning
confidence: 99%
“…Pacientes com córneas mais finas apresentaram maior possibilidade de progressão para glaucoma. Outros estudos mostraram também que pacientes glaucomatosos com córneas mais finas podem ter maior possibilidade de progressão da doença (5)(6) . Tem sido relatado ainda que os pacientes com glaucoma de pressão normal possuem córneas mais finas que indivíduos normais (7) ou portadores de glaucoma primário de ângulo aberto (GPAA), e que hipertensos oculares possuem córneas mais espessas (8) .…”
Section: Introductionunclassified